Description of two new genera of Ochlerini (Hemiptera: Pentatomidae: Discocephalinae) - Garbelotto, Thereza De A.; Grazia, Jocelia; Campos, Luiz Alexandre (Zootaxa, 2019)
Since the phylogenetic analysis of the Herrichella clade (Ochlerini) new genera were described to fit monophyletic groups inferred and considered to be new taxa. The clade I supported by two synapomorphies of the female genitalia, grouped Alitocoris brunneus Sailer together to two new species. Alloeogyna gen. nov. is described here for this clade including the two new species Alloeogyna ampla sp. nov. and Alloeogyna poecila sp. nov. and a new combination is proposed for Alloeogyna brunnea comb. nov.. Also, Alitocoris maculosus Sailer recovered within the clade E in the Herrichella clade is here redescribed in the monotypic Sailerus gen. nov. resulting in the new combination Sailerus maculosus comb. nov..